Coupling Reversible Clustering of DNA‐Coated Gold Nanoparticles with Chemothermal Cycloaddition Reaction. Issue 2 (15th December 2022) - Kruse, Joscha; Sanromán‐Iglesias, Maria; Marauri, Aimar; Rivilla, Ivan; Grzelczak, Marek
Abstract: Stimuli‐responsive, optically‐active colloidal systems are convenient signal transducers capable of monitoring environmental changes at the nanoscale. We report on the coupling of chemo‐thermal cycloaddition reaction with temperature‐sensitive, DNA‐coated gold nanoparticles. We found that the concentration of chemical fuel, dictating the temperature of the mixture, is a primary ingredient in controlling the extent of the reversible clustering of gold nanoparticles. Our results show that rational coupling of chemical and colloidal systems can open up new possibilities in tracking the change of local temperature using aggregation/redispersion of nanoparticles. Abstract : An injection of a fuel into the mixture of DNA‐coated gold nanoparticles leads to their chemo‐thermal redispersion that lasts until the fuel molecules are consumed. Temporal coupling of chemical and colloidal processes set a new framework to link events operating at different length‐scales.